Experimental investigations and modeling of the rubber-asphalt sliding pair dynamics - Božić, Ante (Strojniški vestnik, 2009)
A laboratory model for experimental investigations of the rubber-asphalt sliding pair has been designed to better understand the dynamic behavior of the friction force in the contact patch between the car tire and the road. Its design is described and some experimental results are given. These results confirm that in order to describe friction force in contact between the car tire and the road it is essential to use a dynamic friction model. Moreover, they indicate that the existing dynamic friction models might be physically incorrect in regards to the change of friction coefficient for an asperity bristle passing through the contact surface.
Keywords: pnevmatika; drsenje; trenje; modeli